Socioeconomic status and asthma control in African American youth in SAGE II. (September 2014) - Thakur, Neeta; Martin, Melissa; Castellanos, Elizabeth; Oh, Sam S.; Roth, Lindsey A.; Eng, Celeste; Brigino-Buenaventura, Emerita; Davis, Adam; Meade, Kelley; LeNoir, Michael A.; Farber, Harold J.; Thyne, Shannon; et al.
Abstract Objective: African Americans are disproportionately burdened by asthma. We assessed the individual and joint contribution of socioeconomic status (SES) on asthma morbidity among African American youth. Methods: We examined 686 African Americans (8–21 years) with asthma. To account for the joint effects of SES, a composite index was derived from maternal educational attainment, household income, and insurance status. Ordinal logistic regression was used to estimate the individual and joint effect of SES on asthma control. Models were adjusted for age, sex, controller medication use, in utero smoke exposure, family history of asthma, family history of rhinitis, breastfeeding, daycare attendance, and mold exposure. Results: Participants were classified as Poorly Controlled Asthma (40.8%), Partially Controlled Asthma (29.7%), or Controlled Asthma (30.2%). Of the individual SES indicators, low income was the strongest predictor of poor asthma control. Children with low income had worse asthma control than those with higher income (OR 1.39; 95% CI 0.92–2.12). The SES index ranged from 4–9. SES was associated with 17% increased odds of poor asthma control with each decrease in the index (95% CI 1.05–1.32). The SES index was associated with asthma-related symptoms, nocturnal awakenings, limited activity, and missed school days. Conclusions: The negative effects of SES were observed along the entire socioeconomic gradient, and the adverse asthma outcomes observed in African American youth were not limited to the very poor. We also found that the SES index may be a more consistent and useful predictor of poor asthma outcomes than each indicator alone.